Some problems of solving linear equation with fractions - Stankov, Gordana (Teaching Mathematics and Computer Science, 2006)
The aim of this paper is to offer some possible ways of solving linear equations, using manipulative tools, in which the "−" sign is found in front of an algebraic fraction which has a binomial as a numerator. It is used at 8th grade.